The role of personality factors on job satisfaction among academic staff at public research university - Mehrad, Aida; Hamsan, Hanina; Redzuan, Ma’rof; Abdullah, Haslinda (Universitas Ahmad Dahlan, 2015)
Job satisfaction assumed as a one of the main factor among academic staff and placed as a basic inner feeling for them. Moreover, the purpose of present study was to brilliant the role of job satisfaction at university and illustrated it as a principle positive motivator among academic staff. Lack of consideration to the presence of job satisfaction leads to several difficulties at university and also low level of this inner feeling emerges some insufficient behaviors and reactions among academic staff. Actually, the existence of job satisfaction as basic human needs can develop and support academic staff's performances and conduct their organizational behavior in the accurate way. Furthermore, in current literature review focused on the role and importance of job satisfaction at university and also mentioned its effectiveness on performances, behaviors and reactions of academic staff at educational organization.